THE ROLE OF FOLKLORE IN A MULTICULTURAL WORLD - Bakhtiyar Dilshatovich Bekmatov (Web of Journals Publishing, 2024)
The article analyzes the role of folklore in modern culture, its adaptation to new conditions and the preservation of traditions in the context of globalization. The article considers key aspects of the use of folklore in music, cinema, digital technologies and social media, as well as the impact of global changes on the preservation of the cultural identity of peoples. The article emphasizes the importance of preserving the authenticity of folklore forms when adapting them in popular culture and digital spaces. Examples of successful integrations of folk traditions are given, which contribute to increasing interest in folklore among various audiences, including young people and an international audience.
Keywords: Folklore, modern culture, globalization, digitalization, popular culture, cultural identity, innovation, folk traditions, intercultural communication, preservation of traditions